Kajian Feminisme dalam Cerpen “Mak Ipah dan Bunga-bunga” Karya Intan Paramaditha dalam Kumpulan Cerpen Sihir Perempuan - Aulia Nurkholifah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This study aims to describe the forms of gender inequality of the main character. Gender differences are formed by many things that are socialized, taught, and then constructed in a custom. The gender gap that is formed in customs prevents women do not get injustice from men or appear in the characters of Mak Ipah and Bunga-Bunga short stories they are Intan Paramaditha's. The research method is a qualitative descriptive method with a feminist literary criticism approach: based on the results of data analysis, conclusions are as follows: The form of structure in the short stories of Mak Ipah and Bunga-Bunga by Intan Paramaditha has 8 storylines and 59 sequels of plot, the form of marginalization in the short stories of Mak Ipah dan Bunga-bunga by Intan Paramaditha is in the form of stereotypes (a placement of women with behavior formation and physical), violence that includes domestic violence (physical violence and non-physical violence), and harassment against women.